Awal Kehadiran Peradaban Islam di Indonesia: Eksplorasi Arkeologis Situs Bongal di Tapanuli Tengah - Amelia, Pidia; Azhari, Ichwan; Sari, Ika Purnama (Jurnal Sejarah Citra Lekha, 2025)
The Bongal site in Central Tapanuli preserves important archaeological evidence of early interactions between the Indonesian Archipelago and the Islamic world during the 7th–10th centuries CE. Excavations at the site have yielded a range of early Islamic artifacts, including glass beads associated with Fustat and Nishapur, Umayyad and Abbasid coins, rings bearing Arabic inscriptions, bronze perfume containers, glazed earthenware and glassware from West Asia, as well as medical and chemical instruments. This study aims to reconstruct the earliest presence of Islamic civilization in Indonesia by examining the role of Bongal as a port within the Indian Ocean trade network. The research employs a literature review, comparative analysis with archaeological findings from West Asia and Southeast Asia, and direct observation of collections housed at the Museum of the History of the Qur’an of North Sumatra. The results indicate that Bongal functioned not only as a distribution center for aromatic commodities such as camphor and benzoin, but also as a conduit for the transmission of technology, religious symbols, and Islamic material culture. These findings support the conclusion that the early Islamization of Indonesia occurred primarily through peaceful commercial interactions, positioning Bongal as one of the earliest gateways of Islamic civilization in the archipelago.